The Possibility of Building a Conceptual Framework for Audit theory and its Reflection on Improving the Practice of the Profession: A Survey Study of the opinions of a Sample of Academics and Auditors in the Kurdistan Region of Iraq - خالد مصطفى بهار; فؤاد محمد هەلبەست (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The aim of this research is to analyze the relationship and impact between voluntary disclosure of sustainability reports and the improvement of the informational content of financial reports. After reviewing a collection of studies and literature, theoretical concepts were developed, and a model and hypotheses were built based on voluntary disclosure, sustainability reports, and the informational content of financial reports. Given the nature of the research and its objectives, a descriptive-analytical approach was adopted. To collect data, a questionnaire was used, which was distributed directly to all members of the community represented by employees working in industrial companies in various job positions in the province (city) of Sulaymaniyah. The total number of employees was 157. The researchers distributed 157 questionnaire forms after careful follow-up, and 144 questionnaires were retrieved after verification (19) questionnaires were excluded as they were not suitable for statistical analysis, leaving only 125 valid questionnaires that were used in the statistical analysis. Therefore, the research sample consisted of 125 individuals. Several statistical methods were used, including Cronbach’s Alpha to ensure reliability and validity, and simple correlation analysis to find the relationship and simple regression analysis to determine the impact between variables using SPSS version 24. The results showed a correlation and an impact between the research variables, based on the most important results in the study, several recommendations were made regarding the necessity for industrial companies to focus on voluntary disclosure of sustainability reports in order to achieve their impact on improving the informational content of financial reports. Suggestions for future studies in this field were also provided.